Pemberdayaan Masyarakat melalui Edukasi Pola Makan untuk Pencegahan Diabetes Melitus dan Pelatihan Pembuatan Bolu Kukus Kabocha - Daniek Viviandhari; Maifitrianti Maifitrianti; Lusi Putri Dwita (Universitas Mathla'ul Anwar Banten, 2020)
COMMUNITY EMPOWERMENT THROUGH DIETARY HABIT EDUCATION FOR TYPE 2 DIABETES MELLITUS PREVENTION AND TRAINING OF KABOCHA STEAM CAKE PRODUCT. Riskesdas 2018 data showed that Jakarta was ranked first as the city with the highest prevalence of diabetes mellitus in Indonesia. A high calories and saturated fat diet but lack of physical activity is thought to be a major cause of Jakarta's population at high risk of developing diabetes mellitus. At present the Jakarta population's awareness of a healthy lifestyle is still low. This community service activity aimed to increase PKK's member knowledge of good dietary arrangements and to provide skills to PKK RT 010 RW 005 Malaka Sari Districts, East Jakarta on the making of kabocha steamed cake, with the hope of increasing the economic value of kabocha. In this activity, interactive counseling and demonstration methods were used. The evaluation results from the community service activities showed that participants experienced an improvement in the BMI score, this was supported by data that 80% of participants had adopted a healthy diet. In addition, there was an increase in participants' knowledge about kabocha, diabetes mellitus, and good dietary arrangements to prevent diabetes mellitus. All participants felt their knowledge about the efficacy of kabocha increased, considered the training to be a useful activity, and was also interested in making kabocha steamed cake. Most of the participants were interested in making kabocha steamed cake as a business opportunity to improve the family's economy.